Effect of Crude Extract from the Sea Anemone Bunodeopsis globulifera on Voltage-Gated Ion Channels from Central and Peripheral Murine Nervous Systems - Aleida Jeannette Flores-Pérez; Santiago Loya-López; Arturo Ávalos-Fuentes; Aida Calderon-Rivera; Elisa Damo; Fernando Lazcano-Pérez; Rajesh Khanna; Benjamin Florán-Garduño; Judith Sánchez-Rodríguez (MDPI AG, 2024)
Sea anemones are an important source of bioactive compounds with potential pharmacological applications. Their toxins are produced and stored in organelles called nematocysts and act on specific targets, including voltage-gated ion channels. To date, sea anemone toxins have demonstrated effects on voltage-gated sodium and potassium channels, facilitating investigations into the structure and function of these proteins. In this study, we evaluated the effect of Bunodeopsis globulifera sea anemone crude extract, and of a low molecular weight fraction, on voltage-gated sodium and calcium channels within the murine nervous system. Notably, the crude extract led to a significant reduction in total sodium current, while also triggering calcium-dependent glutamate release. Furthermore, the low molecular weight fraction, in particular, enhanced total calcium currents and current density. These findings underscore the existence of sea anemone toxins with diverse mechanisms of action beyond those previously documented.